STRATEGI PENGUATAN KAPASITAS KELOMPOK TANI HUTAN KEMASYARAKATAN DI DESA BUKIT TINGGI KABUPATEN LOMBOK BARAT - Markum; Sekartaji, Diajeng Aulya; Setiawan, Budhy (JURNAL RIMBA LESTARI, 2022)
This study aims to determine the conditions, analyzed internal-extenal factors and building strategy for strengthening the capacity of community forest group in Batu Kemalik, Bukit Tinggi Village, West Lombok District. SWOT matrix, IFE and EFE matrix and Grand Strategy was used for this study analysis. The sample determination using cluster sampling or sample of groups. The number of samples in this study were 33 respondents who divided into five clusters, consisting of HKm Wana Lestari administrators, members of HKm Wana Lestari, Bukit Tinggi Village officials, BPD Bukit Tinggi, and West Rinjani Forest Management Unit officials. All of the data collected using questionnaires, documentation, and in-depth interviews. Based on the results, it is known that there are 3 factors of internal strength, 4 factors of internal weaknesses, 3 factors of external opportunities and 3 factors of external threats. In general, the group are in a weak position internally so the group have not been able to maximize their strengths to overcome weaknesses, also have not been effective in taking advantage from opportunities and minimizing existing threats. The group institutions are in quadrant I. Several best strategies that can be used are increasing human resources, market development, backward integration, concentric diversification and facilities intercalation.